An EGFP Knock-in Zebrafish Experimental Model Used in Evaluation of the Amantadine Drug Safety During Early Cardiogenesis - Ouyang, Shi; Qin, Wu-Ming; Niu, Yu-Juan; Ding, Yong-He; Deng, Yun (Frontiers in Cardiovascular Medicine, 2022)
Background: Drug exposure during gestation or in prematurely born children represents a significant risk to congenital heart disease (CHD). Amantadine is an antiviral agent also effective in the treatment of Parkinson’s disease. However, while its potential side effects associated with Tetralogy of Fallot (ToF) and birth defects were implicated, its underlying etiologic mechanisms of action remain unknown. Here, we report teratogenic effects of amantadine drug during early cardiogenesis through developing a novel zebrafish (Danio rerio) knock-in (KI) animal model and explore the underlying mechanisms. Methods: Homologous recombination (HR) pathway triggered by CRISPR/Cas9 system was utilized to generate an EGFP KI zebrafish animal model. Dynamic fluorescence imaging coupled with whole-mount in situ hybridization (WISH) assay was employed to compare the spatial and temporal expression patterns of the EGFP reporter in the KI animal model with the KI targeted endogenous gene. Heart morphology and EGFP expression dynamics in the KI animal models was monitored to assess cardiac side effects of different doses of amantadine hydrochloride. Expression of key genes required for myocardium differentiation and left-right (LR) asymmetry were analyzed using WISH and quantitative RT- PCR. Results: A novel EGFP KI line targeted at the vmhc gene locus was successfully generated, in which EGFP reporter could faithfully recapitulate the endogenous expression dynamics of the ventricle chamber-specific expression of vmhc gene. Amantadine drug treatment induced ectopic expression of vmhc gene in the atrium and caused cardiac looping or LR asymmetry defects dose dependently during early cardiogenesis, concomitant with dramatically reduced expression levels of key genes required for myocardium differentiation and LR asymmetry. Conclusion：We generated a novel zebrafish KI animal model in which EGFP reports the ventricle chamber-specific expression of vmhc gene dynamics that is useful to effectively assess drug safety on cardiac morphology in vivo. Specifically, this study identified teratogenic effects of amantadine drug during early cardiogenesis dose dependently, which could be likely conveyed by inhibiting expression of key genes required for cardiac myocardium differentiation and LR asymmetry.